Physics At Home: A Solution to Improve Physics Learning Outcomes during the Covid-19 Pandemic - Rita Aprilyawati; Ahmad Naufal Umam (Online Learning In Educational Research (OLER), 2023)
Physics learning during the COVID-19 pandemic has its challenges. One of them is decreasing student engagement which impacts learning outcomes. Therefore, a learning strategy is needed to overcome this problem. One is implementing a learning strategy that shows physics is a part of daily life. This research was conducted to determine how applying Physics at Home can improve learning outcomes. The design of this research is a quasi-experiment with one group pretest-posttest design. 36 Students of XII IPA 1 SMA Negeri 2 Bandar Lampung received a learning treatment called Physics at Home. The result of this research was the improvement of learning outcomes due to the application of Physics at Home. So it can be concluded that this learning could solve physics learning during the Covid-19 pandemic.